2014
DOI: 10.1016/j.febslet.2014.03.043
|View full text |Cite
|
Sign up to set email alerts
|

Farnesyl‐diphosphate farnesyltransferase 1 regulates hepatitis C virus propagation

Abstract: a b s t r a c tTo identify the novel genes involved in lipid metabolism and lipid droplet formation that may play important roles in Hepatitis C virus (HCV) propagation, we have screened the small interfering RNA library using cell culture derived HCV (HCVcc)-infected cells. We selected and characterized the gene encoding farnesyl-diphosphate farnesyltransferase 1 (FDFT1). siRNA-mediated knockdown of FDFT1 impaired HCV replication in both subgenomic replicon and HCVcc infected cells. Moreover, YM-53601, an inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 30 publications
(40 reference statements)
3
13
0
Order By: Relevance
“…1) plays an important role in the HCV life cycle. This conclusion is consistent with recent studies showing that inhibition of oxidosqualene cyclase, lanosterol C 14 -demethylase, 24-dehydrocholesterol reductase, 7-dehydrocholesterol reductase, and SQS (discussed below) leads to decreased HCV production (31)(32)(33)62). Furthermore, we propose that SQS is a potential target for anti-HCV strategies because all the SQS inhibitors tested in this study exerted anti-HCV effects.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…1) plays an important role in the HCV life cycle. This conclusion is consistent with recent studies showing that inhibition of oxidosqualene cyclase, lanosterol C 14 -demethylase, 24-dehydrocholesterol reductase, 7-dehydrocholesterol reductase, and SQS (discussed below) leads to decreased HCV production (31)(32)(33)62). Furthermore, we propose that SQS is a potential target for anti-HCV strategies because all the SQS inhibitors tested in this study exerted anti-HCV effects.…”
Section: Discussionsupporting
confidence: 93%
“…Our data provide evidence that the committed pathway of cholesterol biosynthesis is important for HCV production, consistent with recent studies (31)(32)(33)62). Moreover, we found that biosynthesis of cholesterol, but not of cholesteryl esters, is important for this process.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…By employing an siRNA library screening in HCVcc-infected cells, we have recently identified 10 host genes that might control lipid metabolism and lipid droplet formation (8). Of these, we selected SCD1 and investigated the functional involvement of SCD1 in HCV propagation.…”
Section: Scd1 Is Required For Hcv Replicationmentioning
confidence: 99%
“…Therefore, targeting host lipid metabolism could be an effective strategy to develop therapeutic agents for HCV-mediated liver diseases. Recently, we screened a small interfering RNA (siRNA) library targeting 114 genes that control lipid metabolism and lipid droplet formation in cell culture-grown HCV (HCVcc)-infected cells and identified 10 pools as candidate hits (8). In the present study, we selected stearoyl coenzyme A (CoA) desaturase 1 (SCD1) for further characterization.…”
mentioning
confidence: 99%